(untitled) (Research, Society and Development, 2020)
Pilomatricoma, also known as a calcifying epithelioma of Malherbe, is a rare beningn cutaneous neoplasm, originated in the cells of the hair follicle matrix which arises in most cases during childhood or adolescence. Clinically it frequently presents as asymptomatic nodules, with coloration generally similar to normal skin, located predominantly in the head, neck or upper extremities, usually hard consistency, slow growth and in most cases solitary. Surgical excision is generally recommended for pilomatricomas to prevent their growth or aesthetic compromise and, as a rule, there is no relapse. The present report aims to present a case of pilomatricoma and its intraoral surgical approach, as well as to discuss relevant literature on the subject. The case report describes a patient complaining of a nodule on the cheek. The pathology diagnosed pilomatricoma. After surgery, the patient evolved without complications, being followed up in the outpatient clinic. Because it presents extensive possibilities of differential diagnosis, isolated clinical diagnosis becomes difficult. Therefore, it is important that the professional is familiar with this neoplasm.